Chemoprotection by Kolaviron of Garcinia kola in Benzene-induced leukemogenesis in Wistar rats. Issue 1 (31st December 2022) - Ola, Olaniyi Solomon; Ogunkanmbi, Esther Oladayo; Opeodu, Emmanuel Babatife
ABSTRACT: Kolaviron (KV) is a biflavonoid phytoconstituent of defatted Garcinia kola seeds that possessed antiproliferative and pharmacological activities. Benzene is an industrial solvent that, however, constitutes occupation hazard, leading to hematological disturbance and leukemia. Therefore, the potency of kolaviron against benzene-induced hematological and myeloid toxicity leading to leukemia was investigated in a rat model. Preleukemic conditions were induced in Wistar rats by intravenous administration of benzene solution. Following induction, 200 mg/kg kolaviron was administered orally for seven days. Hematological parameters, percentage blast cell occurrence and blood cell morphology were compared between baseline control and leukemic rats with or without kolaviron treatment. Plasma activity of arylesterase of paraoxonase-1, total thiol and advanced oxidation protein products (AOPPs) along with clastogenicity and bone marrow architecture was assessed. Kolaviron restored altered hematology, reduced the occurrence of blasts and improved blood cell morphology. Kolaviron also decreased levels of AOPPs, increased total thiol, improved arylesterase activity and mitigated clastogenicity and dysplasia induced in leukemic rats. In conclusion, kolaviron protected against benzene-induced hematological and myeloid toxicities that are implicated in leukemia. Graphical Abstract: uf0001